The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00192-012-1942-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of a single-incision sling and a transobturator sling: clinical efficacy and urodynamic changes

Abstract: These results suggest that the single-incision sling and the transobturator sling are equally as effective and safe for the treatment of stress incontinence, as evaluated during the 1-year follow-up. The insertion of a single-incision sling seems to be less painful than that of a conventional sling. One year after surgery, the MUCP and mean flow rate of the transobturator sling group had significantly decreased compared with that of the single-incision sling group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This is in line with other studies [24,25]. As SIMS needs to be tensioned slightly tighter, higher de novo urgency rates have been reported [26].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with other studies [24,25]. As SIMS needs to be tensioned slightly tighter, higher de novo urgency rates have been reported [26].…”
Section: Discussionsupporting
confidence: 88%
“… 10 Moreover, recent studies have shown that a low MUCP was associated with a failure of surgery for SUI in women. 11 , 12 The results of our study revealed that the AUL was observed to positively correlate with the MUCP.…”
Section: Discussionsupporting
confidence: 50%
“…It also showed that after the mini-sling surgery, the patients experience less pain in comparison to TOT; also 1 year after surgery, the maximal urethral closure pressure (MUCP) and mean Qmax showed a greater decline in the TOT group compared to the mini-sling group. 12 In a study by Wu et al 13 from 2005 to 2014 in Taiwan on 122 women with stress urinary incontinence, the two methods of TOT and mini-sling showed similar results regarding surgical outcomes and urodynamic indices except for a longer surgical time and hospitalization period, more bleeding, and a higher risk of incontinence in the TOT group. Given urinary incontinence which was not reported in 80 patients of the mentioned study, the findings were consistent with our results from other aspects.…”
Section: Discussionmentioning
confidence: 94%
“…It also showed that after the mini-sling surgery, the patients experience less pain in comparison to TOT; also 1 year after surgery, the maximal urethral closure pressure (MUCP) and mean Qmax showed a greater decline in the TOT group compared to the mini-sling group. 12…”
Section: Discussionmentioning
confidence: 99%